Darwin and Design - Ruse, Michael (Filozoficzne Aspekty Genezy, 2022)
The argument from design, the proof of the existence of God from the design-like nature of the world, especially organisms, dates back to Plato in the Phaedo. Despite problems, namely the existence of evil, thanks particularly to Archdeacon William Paley’s Natural Theology, the argument was highly influential in British thought at the beginning of the nineteenth century. Charles Darwin’s theory of evolution through natural selection, as given in his Origin of Species, challenged this hegemony. It is important to note what Darwin did and did not challenge. He accepted fully that organisms are design-like; that, in the language of Aristotle, they show “final causes”. Natural selection explains why this is so. He denied that this feature demands the hypothesis of a designing consciousness, namely God. Darwin was an agnostic, so did not want to deny the existence of God as such. Rather, he thought that the argument failed to prove this. Darwin’s conclusion has led to much subsequent discussion. Generally, however, the world — including Christians — agrees with him. In the words of the English theologian John Henry Newman, as a Christian one can accept that God explains design, one cannot accept that design proves God.